Modelo de desarrollo de turismo sostenible para comunidades rurales del cantón Bolívar - Mero Fuentes, Romina Anabella (2021)
The objective of this research was the making of a sustainable tourism development model that contributes to the rural communities of Bolívar canton; it is qualitative since in the first instance was based on the collection of data for the development of the research, the approach is descriptive because a comprehensive analysis of the territory was carried out based on field observation where the communities could be identified with tourist potential. For this research, a methodological process was structured that consisted of three phases, in the first instance, the comprehensive analysis of the territory was carried out, resulting in the identification of the communities with the greatest tourist potential, which was obtained through tools such as bibliographic review and field work, community characterization file, potentialities file, SWOT matrix, EFI and EFE matrix, in the second phase the validation of criteria and procedures was obtained by 18 experts related to tourism and sustainability, the used tool was a questionnaire interview applied through google forms; finally, in the third phase, the sustainable tourism development model was elaborated, where the purposes, objectives and goals were defined, establishing guidelines and actions, resulting in the structuring and description of the sustainable tourism development model. The purpose of this model is for communities to adopt sustainability as an essential part of community tourism, contributing to the preservation and environmental awareness of each of the inhabitants and tourists.